2018
DOI: 10.1111/spsr.12327
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Cultural Issues as an Opportunity for the Right? Insights from the 2015 Swiss Election

Abstract: This article presents an explanation for the success of the right in the 2015 Swiss parliamentary election based on the spatial model of voting. Since there is no party combining economically left with culturally authoritarian policy stances, voters with that preference combination face a difficult electoral choice. We show that they are more likely to abstain, and that those voters who turn out are more likely to cast votes for the right who represents them on cultural issues. We argue that this behavior is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Citizens can select candidates within parties from comparatively long lists, and in Switzerland the panachage option does not even require a voter to restrict support to politicians of just one party (Bühlmann et al, 2016; Selb & Lutz, 2015). In principle, these electoral rules provide an ideal ground for choosing a set of candidates that share a voter's views, even in a complex policy space with multiple issue dimensions (Kurella & Rosset, 2018).…”
Section: Plenty Of Choice – Enough Information?mentioning
confidence: 99%
“…Citizens can select candidates within parties from comparatively long lists, and in Switzerland the panachage option does not even require a voter to restrict support to politicians of just one party (Bühlmann et al, 2016; Selb & Lutz, 2015). In principle, these electoral rules provide an ideal ground for choosing a set of candidates that share a voter's views, even in a complex policy space with multiple issue dimensions (Kurella & Rosset, 2018).…”
Section: Plenty Of Choice – Enough Information?mentioning
confidence: 99%
“…Much of the literature has focused on voters combining conservative stances on cultural issues with statist preferences regarding the role of the state in the economy, often labelled authoritarian-left (e.g. Lipset 1960) and found that they have a hard time finding a party representing them and are more likely to abstain (see e.g., Lefkofridi et al 2014, Kurella and Rosset 2017, Kurella and Rosset 2018. While the consequences of abstention with respect to policy representation are clear and severe, in the following we explicitly focus on those voters who decide to turn out to vote.…”
Section: Policy Voting By Incomementioning
confidence: 99%
“…Therefore, they will face a more difficult vote decision, since they are likely torn between two parties from opposing camps, each representing their policy ideals closely on one policy area but presenting opposing proposals in the other policy area. Much of the literature has focused on voters combining conservative stances on cultural issues with statist preferences regarding the role of the state in the economy, often labelled authoritarian-left (Lipset 1960) and found that they have a hard time finding a party representing them and are more likely to abstain (Lefkofridi et al 2014;Kurella & Rosset 2018;Hillen & Steiner 2020). While the consequences of abstention with respect to policy representation are clear and severe (Verba et al 1995;Lijphart 1997), in the following we explicitly focus on those voters who decide to turn out to vote.…”
Section: Policy Voting By Incomementioning
confidence: 99%
“…Wüest ( 2018 ) links the Selects voter surveys to the media analysis to assess the influence of the information environment on voters’ perceptions of the most important political problems. Kurella and Rosset ( 2018 ) integrate information from the candidate survey to their analysis of the post‐election survey while Petitpas and Sciarini ( 2018 ) fully exploit the three waves of the panel survey to study the short‐term changes in the way voters evaluate the competences of parties on specific issues. Other contributions link the Selects data with external data sources.…”
Section: Methodological Innovations In the Study Of Swiss Electoral Rmentioning
confidence: 99%